POLA KONSUMSI SANTRI DALAM PERSPEKTIFHALAL LIFE STYLE - Amimi, Aisyah; Dahruji, Dahruji; Mashudi, Mashudi (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
This study aims to analyze the consumption patterns of Islamic boarding school students in the perspective of a halal lifestyle. In the context of Islam, consumption is not only seen in terms of fulfilling physical needs, but also as a means to achieve happiness in this world and the hereafter. This study examines how Islamic boarding school students apply halal principles in their daily consumption activities. The method used in this study is a qualitative approach with data collection through interviews and observations at Islamic boarding schools in Sumenep, Madura. The results of the study are expected to provide new insights into the awareness and practice of halal consumption among Islamic boarding school students, as well as contribute to the development of halal literacy in society. This study also aims to encourage students to understand existing social problems and find relevant solutions. The location of the study will be carried out at the Nurul Islam Karangcempaka Islamic Boarding School and the Hidayatullah Islamic Boarding School in Sumenep, Madura.